2015
DOI: 10.1007/s10867-015-9387-y
|View full text |Cite
|
Sign up to set email alerts
|

Laser interferometric investigation of solute transport through membrane-concentration boundary layer system

Abstract: We investigate diffusive transport in a membrane system with a horizontally mounted membrane under concentration polarization conditions performed by a laser interferometry method. The data obtained from two different theoretical models are compared to the experimental results of the substance flux. In the first model, the membrane is considered as infinitely thin, while in the second one as a wall of finite thickness. The theoretical calculations show sufficient correspondence with the experimental results. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…( 22 ), it is easy to calculate the spatial formula ζ s = f ( R C , J vm ), allowing the evaluation of the numerical relations between the concentration polarization coefficient ( ζ s ), the osmotic flux ( J vm ) and the concentration Rayleigh number ( R C ). The results of the research carried out confirmed the significant role of concentration boundary layers in osmotic and diffusive transport, in particular their applicative aspect in technology and medicine, as mentioned in the Introduction [ 5 , 32 34 ]. The obtained results of the test are also significant for micro-gravitation conditions under which membrane transport and transport in areas near the membrane are of non-linear diffusive character.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…( 22 ), it is easy to calculate the spatial formula ζ s = f ( R C , J vm ), allowing the evaluation of the numerical relations between the concentration polarization coefficient ( ζ s ), the osmotic flux ( J vm ) and the concentration Rayleigh number ( R C ). The results of the research carried out confirmed the significant role of concentration boundary layers in osmotic and diffusive transport, in particular their applicative aspect in technology and medicine, as mentioned in the Introduction [ 5 , 32 34 ]. The obtained results of the test are also significant for micro-gravitation conditions under which membrane transport and transport in areas near the membrane are of non-linear diffusive character.…”
Section: Discussionsupporting
confidence: 65%
“…The obtained results of the test are also significant for micro-gravitation conditions under which membrane transport and transport in areas near the membrane are of non-linear diffusive character. Under such conditions, by suppressing natural convection and/or by suppressing sedimentation, the character of the transport of oxygen and nutrients may change, thereby causing metabolism disorders [ 5 , 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nephrophane (VEB Filmfabrik, Wolfen, Germany) is a microporous, highly hydrophilic membrane made from cellulose acetate ([trio-acetate cel-(OCO-CH 3 )n]) of a spongy structure4068. The analysis of biofilm degradation by intact and UV-inactivated phages was performed by microbiological methods as well as biophysical techniques.…”
Section: Methodsmentioning
confidence: 99%